2004
DOI: 10.1088/0953-4075/37/24/011
|View full text |Cite
|
Sign up to set email alerts
|

Critical minimum in elastic electron scattering by krypton

Abstract: The position of the critical minimum in elastic electron–krypton scattering at intermediate electron energies was investigated. Differential cross sections (DCSs) were measured as a function of both incident electron energy (100–260 eV) and scattering angle (30–110°), in small steps around the critical minimum. The energy dependence of the angular positions of DCS minima were determined. Also, the positions of minima in energy-dependent DCSs were obtained at several fixed scattering angles close to the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 12 publications
5
44
2
Order By: Relevance
“…This conclusion is based on a detailed experimental investigation of incident beam profile and technical characteristics of the experimental system, according to the work of Brinkmann and Trajmar (1981). Also, it was confirmed by comparing DCSs for Ar and Kr with a number of previous experimental results (see Milosavljević et al (2004aMilosavljević et al ( , 2004b, this work). During the measurements, all the parameters were kept in the range where the contribution of double electron scattering was negligible.…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…This conclusion is based on a detailed experimental investigation of incident beam profile and technical characteristics of the experimental system, according to the work of Brinkmann and Trajmar (1981). Also, it was confirmed by comparing DCSs for Ar and Kr with a number of previous experimental results (see Milosavljević et al (2004aMilosavljević et al ( , 2004b, this work). During the measurements, all the parameters were kept in the range where the contribution of double electron scattering was negligible.…”
Section: Methodssupporting
confidence: 67%
“…The energy resolution was about 1 eV, as measured at the FWHM (full-width at half maximum) of the elastic peak. In our previous paper (Milosavljević et al 2004a) it was shown that DCS surface for elastic electron-krypton scattering in this energy range has large energy spread and, in contrast, large gradient along angular axis. Therefore, the main limitation on reaching the deep DCS minima is imposed by finite angular resolution, while in this region the cross sections are rather insensitive to the small changes of incident energy.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the TCSs we identify and delineate the important physical effects such as the Wigner threshold law, Ramsauer-Townsend (RT) minima, shape resonances and BEs of the excited Au À and Pt À anions. The critical minima [26,27] that characterize the DCSs are also extracted from the DCSs and the BEs as well. The TCSs are evaluated using the Mulholland formula [28] implemented through the complex angular momentum (CAM) description of electron-atom scattering while the DCSs are evaluated using a partial wave expansion.…”
Section: Introductionmentioning
confidence: 99%